2013
DOI: 10.4028/www.scientific.net/amm.486.90
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Necessary Geometric Parameters of the Specimen in Ring-Core Method

Abstract: There are several measuring techniques for determining residual stress which can be divided according to the created damage in to the construction in non-destructive, semi-destructive and destructive ones. One of the most common is semi-destructive hole-drilling method. This paper deals about Ring-Core method which is based on the similar principles. Today, there is no standard for the Ring-Core method, thus it is important to consider various influential factors. One of them are the dimensions of specimen. Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 2 publications
0
24
0
Order By: Relevance
“…Therefore the influence of the specimen´s thickness, width and length on the method applicability was the main part of the research. The previous research of incremental method [8] at the authors´ workplace showed, the minimal specimen´s dimensions are 30mm x 40mm x 50mm for residual stress evaluation using universal set of calibration coefficients. Now the minimal specimen´s dimensions for using the integral method are considered.…”
Section: Integral Evaluation Methodsmentioning
confidence: 99%
“…Therefore the influence of the specimen´s thickness, width and length on the method applicability was the main part of the research. The previous research of incremental method [8] at the authors´ workplace showed, the minimal specimen´s dimensions are 30mm x 40mm x 50mm for residual stress evaluation using universal set of calibration coefficients. Now the minimal specimen´s dimensions for using the integral method are considered.…”
Section: Integral Evaluation Methodsmentioning
confidence: 99%
“…Thus the method is suitable for the evaluation of residual stress uniformly distributed through the model thickness. The strain gage sensitivity to the inner stress is determined by the calibration coefficients K 1 , K 2 calculated by equations (2)-(5) [1,8].…”
Section: Incremental Methodsmentioning
confidence: 99%
“…From published works it is known that only one universal set of calculation coefficients is needed, which is unique for specific material parameters, type of strain gage rosette and the parameters of created notch, to determine the direction, sense and magnitude of the residual stress components inside the component [1,4,5,6,7]. Thus the simple model of a cube with sufficiently large dimensions to avoid unwanted boundary influences on calculation accuracy was chosen as a simulation model.…”
Section: Simulation Model In Solidworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Hole-drilling is a well-established procedure defined by internationally accepted standards. 1,2 Ring-core was introduced more than 20 years ago; [3][4][5][6] however, it was deeply investigated and developed only recently, especially in terms of sensitivity and uncertainty analysis, [7][8][9][10] and even applied at the microscale. 11,12 In hole-drilling, the material is removed at the centre of a rosette, and thus the relaxed strains are measured at the periphery of the hole, whereas in ring-core the strains are measured in the central internal region, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%